2000
DOI: 10.1007/pl00008149
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of the maize Zm-p60.1 gene encoding a β-glucosidase located to plastids

Abstract: A beta-glucosidase that cleaves the biologically inactive hormone conjugates cytokinin-O- and kinetin-N3-glucosides is encoded by the maize Zm-p60.1 gene. The expression of the Zm-p60.1 gene was analyzed by Northern blot analysis and in-situ hybridization. It was found that the expression levels of the Zm-p60.1-specific mRNA changed after pollination of carpellate inflorescences. The Zm-p60.1 cDNA was expressed in E. coli and antibodies were raised against this protein. An antibody was used to determine the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…β-Glycosidases activate β-glycosides, secondary metabolites that perform a wide array of cellular functions including the induction of symbiosis, breakdown of endosperm cell wall during germination, phytohormone activation, lignification, the production of aromatic compounds and defense (Nisius 1988;Poulton 1990;Dharmawardhana et al 1995;Leah et al 1995;Hungria & Stacey 1997;Kristoffersen et al 2000;Mizutani et al 2002;Morant et al 2003;Fia et al 2005;Maicas & Mateo 2005;Escamilla-Trevino et al 2006;Halkier & Gershenzon 2006;Lee et al 2006;Suzuki et al 2006;Naoumkina et al 2007;Stauber et al 2012). Some of the defense β-glycosides include α-hydroxynitrile glucosides, benzoxazinoid glycosides, avenacosides, isoflavonoid glycosides and glucosinolates (Niemeyer 1988;Nisius 1988;Poulton 1990;Cairns et al 2000;Halkier & Gershenzon, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…β-Glycosidases activate β-glycosides, secondary metabolites that perform a wide array of cellular functions including the induction of symbiosis, breakdown of endosperm cell wall during germination, phytohormone activation, lignification, the production of aromatic compounds and defense (Nisius 1988;Poulton 1990;Dharmawardhana et al 1995;Leah et al 1995;Hungria & Stacey 1997;Kristoffersen et al 2000;Mizutani et al 2002;Morant et al 2003;Fia et al 2005;Maicas & Mateo 2005;Escamilla-Trevino et al 2006;Halkier & Gershenzon 2006;Lee et al 2006;Suzuki et al 2006;Naoumkina et al 2007;Stauber et al 2012). Some of the defense β-glycosides include α-hydroxynitrile glucosides, benzoxazinoid glycosides, avenacosides, isoflavonoid glycosides and glucosinolates (Niemeyer 1988;Nisius 1988;Poulton 1990;Cairns et al 2000;Halkier & Gershenzon, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Based on its enzyme activity and highly specific expression pattern, Zm-p60.1 has been suggested to be one of the key enzymes involved in the regulation of plant development by releasing active phytohomornes, cytokinins, from cytokinin-O-glucosides, their inactive storage and transport forms (Brzobohatý et al, 1993;Kristoffersen et al, 2000). Further characterization revealed that Zm-p60.1 dimer formation is an essential prerequisite for obtaining enzyme activity (Rotrekl et al, 1999).…”
mentioning
confidence: 99%
“…Further characterization revealed that Zm-p60.1 dimer formation is an essential prerequisite for obtaining enzyme activity (Rotrekl et al, 1999). The enzyme has been localized to plastids/ chloroplasts (Kristoffersen et al, 2000). As a first step toward addressing the mechanism of catalytic activity and substrate specificity the enzyme was purified, crystallized, and the crystals were subjected to preliminary x-ray analysis (Vévodová et al, 2001).…”
mentioning
confidence: 99%
“…In maize, this enzyme is most active in the coleoptiles, followed by the roots and pistils (Esen 1993;Nikus and Jonsson 1999). It was subsequently shown to be localized in the plastids/chloroplast (Esen and Stetler 1993;Kristoffersen et al 2000). To date, Zm-p60.1 is the only β-glycosidase that has been introduced into transgenic plants.…”
Section: Reactivationmentioning
confidence: 95%